Evaluacion de la eficacia del losartán de 50 mg en el tratamiento antihipertensivo para adultos mayores. - Azu Peralta, Lilian Estefania (2017)
The present research work performed at the Hospital María Lorena Serrano Aguilar was carried out because older adults do not complete the treatment protocols established in the medical prescription because some because of their advanced age can not read well the indications in the recipe, For lack of information about the correct use of the drug, because they do not feel the immediate pharmacological benefits, and finally discontinued its administration and this allowed us to perform pharmacovigilance that is based on a set of activities that relate to evaluate, understand and prevent The adverse or secondary effects that the drug produces in hypertensive older adults who are administered losartan 50mg as a treatment of choice; Which acts as an AT1 receptor antagonist of angiotensin II (AR-II), which like all medicines has its adverse effects such as: dizziness, fatigue, hyperkalemia, among others, to improve their quality of life, avoiding the irrational use of the drug. Because hypertension in older adults is more frequent, although it can appear at any age between 30 and 50 years, after 10 or 20 years of the disease shows the risks that can cause, Its prevalence has a lot to do with either age or lifestyle. Two conferences were held in which patients were informed of the effects related to pharmacological treatment with losartan (Annex 7.4) and (Annex 7.12), the correct storage and preservation of drugs (Annex 7.9) allows us to obtain treatment efficacy Result the objective of the same. The qualitative method was used as it was based on the sampling and analysis of data obtained by conducting surveys to the elderly patients attended at the Hospital María Lorena Serrano Aguilar with the review of their clinical records that allowed us to tabulate data And to obtain variables analyzed in the statistical program PASW Statistics 18. According to the form of Notifications of Adverse Drug Reactions was identified as new reaction first with 6.33% the tingling of extremities and with a lower rank with 1.27% pain in the pelvic region And rhinorrhea. According to the analysis that was done we found that the most frequent adverse effects with 12.66% are muscular pain in both sexes and compared with the surveys performed, 100% suffer from it; As a second effect are grouped reactions such as muscle pain, headache and cough with 12.65% and in the surveys are also the cough with 80% and the headache with 40%; The only one that varies is the pruritus that according to the analysis of the adverse reaction form is the end with 1.27% while the surveys indicate that it is in third place with 60%. A database was designed for the registration and control of hypertensive patients (Annex 7.2), which is similar to the control of appointments (Annex 7.7). Of all the patients surveyed, 80% require another treatment for the other diseases they suffer Without affecting the effectiveness of Losartan because 80% if you see improvement and according to the form of adverse reactions is at 74.68%, ie losartan is making its therapeutic effect in that population